Recent Progress of Solid Lipid Nanoparticles and Nanostructured Lipid Carriers as Ocular Drug Delivery Platforms - Viliana Gugleva; Velichka Andonova (MDPI AG, 2023)
Sufficient ocular bioavailability is often considered a challenge by the researchers, due to the complex structure of the eye and its protective physiological mechanisms. In addition, the low viscosity of the eye drops and the resulting short ocular residence time further contribute to the observed low drug concentration at the target site. Therefore, various drug delivery platforms are being developed to enhance ocular bioavailability, provide controlled and sustained drug release, reduce the number of applications, and maximize therapy outcomes. Solid lipid nanoparticles (SLNs) and nanostructured lipid carriers (NLCs) exhibit all these benefits, in addition to being biocompatible, biodegradable, and susceptible to sterilization and scale-up. Furthermore, their successive surface modification contributes to prolonged ocular residence time (by adding cationic compounds), enhanced penetration, and improved performance. The review highlights the salient characteristics of SLNs and NLCs concerning ocular drug delivery, and updates the research progress in this area.